COV&R Story - Gans, Eric Lawrence (1999)
I recently returned from Emory University in Atlanta, where I attended the annual meeting of the Girardian Colloquium on Violence and Religion. This year’s topic was "violence reduction in theory and practice." The speaker’s list included a primatologist, an ethnologist, a participant in the South African peace process, and an autodidact writer on the Holocaust,...